High-temperature expansion in self-consistent-field theory of spin-crossover compounds - Gudyma, Iu.V.; Daskal, Ye.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
In the paper, spin-crossover compounds were examined from the viewpoint of
perturbation theory for self-consistent field. The research carried out in the framework of
the Ising-like model for these compounds. We have obtained the first four moments for
the spin state distribution function in contact with environment in a narrow temperature
interval